REKONSTRUKSI NILAI TEO-EKOLOGI HINDU PADA PEMUJAAN PURA ULUN DANU DI BALI - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Today the phenomenon of environmental pollution is increasingly massive. Similarlyin Bali, associated with the existence of existing lakes in Bali, the environmental pollutionphenomenon is also nampat existence. Therefore it is necessary to excavate the magical religioustheological value system which if able to overcome it. Related to this matter, there are twoproblem formulas that will be studied in this paper that is how Hindu Teo-Ecology? and thereconstruction of Hindu Theo-ecology values on the Ulun Danu ritual in Bali?. In this studyusing several theories and methods. The theory used is value theory and ecological theory.Likewise in this study using several motodes and techniques that is in the discovery of data usingobservation methods, interviews, and document studies, while in the data analysis used qualitativedescriptive method.From the Hindu theo-ecological point of view, the following forms of worship are found: (1)Worship Against Dewi Lakshmi, (2) Worship Against Bhatara Jayaningrat, (3) Worship AgainstDewi Danu, (4) Worship of Duwe Ida Betara. Similarly, in relation to the reconstruction of thetheological value, several values are found as follows: (1) Understanding of the Rta Recognizingthe Importance of Maintaining the Environment, (2) Yadnya Restoring Environmental Harmony,(3) Danu Krtih As Effort to Restore the Purity of Lake Water, (4) Awareness In Rwa BhinedaCreating Balance on Nature, (5) Tri Hita Karana Creates Universal Harmony.